“God on Earth”: a Mexican Reception of the Notes from the Underground - Anastasia V. Gladoshchuk (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The paper focuses on two short stories from the collection “God on Earth” (1944) by the Mexican author José Revueltas (1914–1976). The texts are analysed in the perspective suggested by the only epigraph which is a citation from the IX chapter of the first part of Notes from the Underground: “And yet I think man will never renounce real suffering, that is, destruction and chaos”. It is being argued that Revueltas didn’t read Dostoevsky directly but through Lev Shestov’s essay “The Conquest of the Self-Evident” (1921). Forming a conceptual mark, the first (“God on Earth”) and the last (“How great is the darkness?”) stories, whose action takes place at the time of the “cristeros” revolt, develop the motifs of the “underground voice” and the “second vision”, which Shestov deduced from Dostoevsky’s novel. Enclosing God, whose voice is “not one’s one voice” of the underground man, in the realm of “earth”, Revueltas brings the state of the “underground” to the last point of despair, where only “suffering”, “destruction” and “chaos” become possible, where “wellbeing” is denied by “caprice”. In the world Revueltas creates every mortal, turning alternately into “beast” or “god”, finds himself in the “underground”, in accordance with Shestov’s interpretation of the “underground” as Plato’s Cave.